Risk of primary gastrointestinal cancers following incident non-metastatic breast cancer: a Danish population-based cohort study - Henrik Toft Sørensen; Mark R Cullen; Lidia Schapira; Kasper Adelborg; Jens Sundbøll; Dóra Körmendiné Farkas; Suzanne Tamang; Deirdre Cronin-Fenton (BMJ Open Gastroenterology)
Objective We examined the risk of primary gastrointestinal cancers in women with breast cancer and compared this risk with that of the general population.Design Using population-based Danish registries, we conducted a cohort study of women with incident non-metastatic breast cancer (1990–2017). We computed cumulative cancer incidences and standardised incidence ratios (SIRs).Results Among 84 972 patients with breast cancer, we observed 2340 gastrointestinal cancers. After 20 years of follow-up, the cumulative incidence of gastrointestinal cancers was 4%, driven mainly by colon cancers. Only risk of stomach cancer was continually increased beyond 1 year following breast cancer. The SIR for colon cancer was neutral during 2–5 years of follow-up and approximately 1.2-fold increased thereafter. For cancer of the oesophagus, the SIR was increased only during 6–10 years. There was a weak association with pancreas cancer beyond 10 years. Between 1990–2006 and 2007–2017, the 1–10 years SIR estimate decreased and reached unity for upper gastrointestinal cancers (oesophagus, stomach, and small intestine). For lower gastrointestinal cancers (colon, rectum, and anal canal), the SIR estimate was increased only after 2007. No temporal effects were observed for the remaining gastrointestinal cancers. Treatment effects were negligible.Conclusion Breast cancer survivors were at increased risk of oesophagus and stomach cancer, but only before 2007. The risk of colon cancer was increased, but only after 2007.